Impact of coastal aquaculture operation systems in Hainan island (China) on the relative abundance and community structure of Vibrio in adjacent coastal systems. (5th February 2020) - Möller, Lars; Kreikemeyer, Bernd; Luo, Zhu-Hua; Jost, Günter; Labrenz, Matthias
Abstract: The bacterial genus Vibrio is widespread in aquatic systems and contains several pathogenic species. As pathogenic Vibrio infections in aquaculture systems have been documented, the release of untreated aquaculture wastewater could cause the release of high doses of the pathogens into the environment and thus to the replacement of naturally occurring Vibrio populations. Aquaculture is one of the main industries on the island of Hainan (southern China) and the risk of pathogenic Vibrio contamination of the environment and humans is accordingly high. In this study, we used Illumina 16S rRNA gene sequencing of water, sediment, seagrass and tissue samples obtained from aquaculture operations in this region and from adjoining coastal and riverine areas to examine the impact of aquaculture on Vibrio assemblages. The results indicated that the effects of aquaculture on Vibrio community structure and abundance depended on the particular system. Classical pond aquaculture decreased Vibrio diversity and significantly reduced the relative abundances of Vibrio 16S rRNA genes compared to coastal reference populations. Aquaculture systems continuously flushed with marine water had a Vibrio community structure and diversity similar to that of coastal populations but with elevated levels of Vibrio sequence reads. Despite the observed changes, there was no clear evidence that aquaculture facilities altered Vibrio composition or led to a measurable increase in the relative abundance of Vibrio genes in the environment. Graphical abstract: Image 1 Highlights: Aquaculture operation systems influence Vibrio spp. communities in the aquacultures. Pond aquaculture lowers Vibrio diversity. Continuous aquaculture systems increase Vibrio abundance. Aquaculture had no detectable impact on environmental Vibrio populations.